Q: 6a - 5b equals 9 2a plus 5b equals 23?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

8b -2a

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b

ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.

7

Related questions

the answer

2a+5b isn't possible the answer is still 2a+5b.

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b

What is the solution of -2a plus 3a plus 5b

8b -2a

The expression is: (4a+b)/(2a-5b)

2a+6b

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b

10a - 5b = 25 So 5b = 10a - 25 and hence b = 2a - 5

ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.

7